2010
DOI: 10.1016/j.ejcts.2009.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering and biotechnology in general thoracic surgery

Abstract: Public interest in the recent progress of tissue engineering, a special line of biotechnology, makes the current review on thoracic surgery highly relevant. In this article, techniques, materials and cellular processes are discussed alongside their potential applications in tissue repair. Different applications of tissue engineering in tracheo-bronchial replacement, lung tissue cultures and chest-wall reconstruction are also summarised in the article. Potential tissue engineering-based solutions for destructiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…Tamas et al identified four essential cell types crucial for maintaining lung functionality: fibroblast cells, alveolar epithelial cells, endothelial cells, and smooth muscle cells (Figure 1). These cell types encompass both functional cells necessary for normal lung function and structural cells that offer mechanical support [54]. The largest volume of the lung is comprised of an alveolar sac, which is an elaborate sac-like structure composed of epithelial cells surrounded by blood capillaries.…”
Section: Cell Source and Typementioning
confidence: 99%
“…Tamas et al identified four essential cell types crucial for maintaining lung functionality: fibroblast cells, alveolar epithelial cells, endothelial cells, and smooth muscle cells (Figure 1). These cell types encompass both functional cells necessary for normal lung function and structural cells that offer mechanical support [54]. The largest volume of the lung is comprised of an alveolar sac, which is an elaborate sac-like structure composed of epithelial cells surrounded by blood capillaries.…”
Section: Cell Source and Typementioning
confidence: 99%
“…Looking to the future, whilst we do not wish to speculate too much, development in the following areas is possible: robotics, telesurgery, tissue engineering and biotechnology, and total artificial lung [11,12]. Research activities in these and other fields may lead to new solutions to old problems in our specialty.…”
Section: Thoracic Surgery: Highlights Of the Last Two Decadesmentioning
confidence: 99%
“…In addition to this unparalleled success in the development of EJCTS [2][3][4][5][6][7][8][9][10], Ludwig von Segesser launched a second publication in September 2002, Interactive CardioVascular and Thoracic Surgery (ICVTS). This interactive Journal is available to the reader in both a printed and an online version.…”
mentioning
confidence: 99%